The Keys to Happiness : Sex and the Search for Modernity in fin-de-Siecle Russia - Engelstein, Laura (Book collections on Project MUSE., 1992)
[Engelstein's] sensitivity to the interplay of conceptions of gender and class with politics and science makes the book valuable not only to Russianists, but to historians of culture and society in general. ... Laura Engelstein has made a remarkable contribution to the scholarly literature. - Journal of the History of Sexuality.